Using Blended learning to develop skills of Object-oriented programming (OOP) for Faculty of Education students - Salama Elkholy (International Journal of Instructional Technology and Educational Studies)
The recent paper aims at showing the importance of the blended learning to develop skills of Object-oriented programming (OOP) for vocational diploma students of instructional technology at faculty of education. The random study sample was formed of (17) students of the vocational diploma in the year (2018-2019) Two tools were used in the research including an accumulative test to measure the cognitive aspect of Object-oriented programming ( OOP) As for the research findings. The cognitive accumulative test and the note card for the vocational diploma students showed differences with statistical significance at significant level( ≤ 0. 05) between arithmetic means grades in the pre and post applications for the benefit of the post application.